2021
DOI: 10.1186/s12967-021-02764-y
|View full text |Cite
|
Sign up to set email alerts
|

Combination of subtherapeutic anti-TNF dose with dasatinib restores clinical and molecular arthritogenic profiles better than standard anti-TNF treatment

Abstract: Background New medications for Rheumatoid Arthritis (RA) have emerged in the last decades, including Disease Modifying Antirheumatic Drugs (DMARDs) and biologics. However, there is no known cure, since a significant proportion of patients remain or become non-responders to current therapies. The development of new mode-of-action treatment schemes involving combination therapies could prove successful for the treatment of a greater number of RA patients. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
1
5
1
Order By: Relevance
“…Another study demonstrated combination therapy of dasatinib and subtherapeutic dose of TNF inhibitor showed a synergistic anti‐arthritic effect on a Tg197 arthritis mouse model 30 . In the present study, the inhibition of osteoclastogenesis by dasatinib administration was significantly inhibited in the dasatinib pretreatment group, and this was not evaluated in the previous studies 12,30 . The suppression of immunoglobulin and pro‐inflammatory cytokines presented in the previous study 12 was also confirmed in the present study (data not shown).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Another study demonstrated combination therapy of dasatinib and subtherapeutic dose of TNF inhibitor showed a synergistic anti‐arthritic effect on a Tg197 arthritis mouse model 30 . In the present study, the inhibition of osteoclastogenesis by dasatinib administration was significantly inhibited in the dasatinib pretreatment group, and this was not evaluated in the previous studies 12,30 . The suppression of immunoglobulin and pro‐inflammatory cytokines presented in the previous study 12 was also confirmed in the present study (data not shown).…”
Section: Discussionsupporting
confidence: 74%
“…We aimed to compare which effect (preventive versus therapeutic) would be more prominent in the CIA model, and conclude that the preventive role of dasatinib was more evident and was exerted earlier than the therapeutic effects. Another study demonstrated combination therapy of dasatinib and subtherapeutic dose of TNF inhibitor showed a synergistic anti‐arthritic effect on a Tg197 arthritis mouse model 30 . In the present study, the inhibition of osteoclastogenesis by dasatinib administration was significantly inhibited in the dasatinib pretreatment group, and this was not evaluated in the previous studies 12,30 .…”
Section: Discussioncontrasting
confidence: 64%
“…Notably, the new two best NPs identified, although ~5-fold less effective than SPD304, presented much less toxicity on the cells (in the range of two orders of magnitude). Additionally, mostly Nepalensinol B, and to a lesser extent, Miyabenol A, were able to downregulate chemokine ligand 5 (CCL5), which was found to be, among others, a pathogenic chemokine, being used for drug testing, both in human RA [ 88 ] and mouse chronic polyarthritis [ 89 ]. Both Nepalensinol B and Miyabenol A reduced CCL5 in both hTNFtg SFs, which spontaneously secrete high levels of chemokines, and wild-type (WT) SFs exogenously stimulated with human TNF in order to increase their pro-inflammatory potential.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapies carry the advantage of synergic action of both drugs, usually allowing lower doses to be administered. In a recent experimental study, the tyrosine kinase inhibitor dasatinib was co-administered with sub-therapeutic doses (only 10% of the standard dose) of infliximab, adalimumab, golimumab or etanercept in the human TNF-dependent Tg197 arthritis mouse model [ 202 ]. The combination therapy led to amelioration of clinical and histopathological findings of arthritis, which was more profound with the combination of low-dose infliximab and dasatinib, to a degree similar to the therapeutic infliximab dose.…”
Section: Introductionmentioning
confidence: 99%